Between metrics and territory: journals facing a new evaluation cycle - Furlani, João Carlos; Cattafesta, Monica (Guará Journal, 2025)
This editorial presents the transformations undergone by Revista Guará throughout 2025 and discusses the evaluative horizon now opening before Brazilian scientific journals. It records the revision of editorial norms and policies, the submission to new indexing services, the redesign of the graphic project, the adoption of continuous publication flow in place of biannual periodicity, and the attainment of the A1 classification in the Qualis Periódicos system for the 2021 to 2024 quadrennium. It argues that this recognition arrives at the very moment in which Capes replaces the classification of venues with the classification of articles, a circumstance that calls for a reading more analytical than celebratory. It then discusses the risks of uncritical adherence to metrics, the asymmetrical coverage of major indexing services with respect to Latin American journals, and the absence of university extension as an autonomous area of evaluation within Capes. It holds that extension knowledge is always situated and that to internationalise cannot mean to deterritorialise. It concludes by defending a position of discernment, one that refuses neither editorial improvement nor the pursuit of indexation, but recalls that the ultimate purpose of an extension journal is to qualify and render visible the encounter between the university and society.